ANALISIS KORUPSI DAN UPAYA MEWUJUDKAN GOOD GOVERNANCE DI INDONESIA - Neova Derenov Budhi Arti; Ratih Yanuar Rizky (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2023)
The government system in Indonesia is constantly improving from time to time in order to create good governance for all Indonesian people. Efforts to realize Good Governance have been carried out by the government through making policies. Good governance for various reasons is considered as an ideal government concept to be applied in Indonesia. The emphasis on public participation in government is in line with the democratic system implemented in Indonesia. The contribution of the community in government will certainly have a good impact on the government itself. The development of Good Governance has begun during the reform of the Indonesian nation, but until now, good governance has not been successfully implemented in Indonesia. Various problems are still often faced by the Indonesian people in their efforts to realize Good Governance